Bioreaction engineering modeling and control - Schügerl, Karl 1927-2018; Bellgardt, Karl-Heinz (Springer Berlin Heidelberg, 2000)
The book is intended to present various examples for reactor and process modeling and control as well as for metabolic flux analysis and metabolic design at an ad vanced level. In Part A, General principles and techniques with regard to reactor and process models, process control, and metabolic flux analysis are presented. In addition the accuracy, precision, and reliability of the measured data are discussed which are ex tremely important for process modeling and control. A virtual bioreactor system is presented as well, which can be used for the training of students and operators of industrial plants and for the development of advanced automation tools. In Part B, the General principles are applied for particular bioreactor models. It covers the application of the computational fluiddynamic (CFD) technique to stirred tank and bubble column bioreactors. Different solution methods are presented: the Reynolds-averaging of the turbulent Navier-Stokes equations and modeling of the Reynolds stresses with an appropriate turbulence (k-ee) model, and the Euler (two fluid model), as well as the Euler-Langrange approaches
Keywords: Chemistry; Industrial Chemistry/Chemical Engineering; Biotechnology; Microbiology; Chemical engineering; Bioreaktor; Prozessmodell; Prozessüberwachung; Biotechnologie; Reaktionstechnik